Simplify (8m - 4n) + (6m + 3n).

Question

Asked 6/23/2016 11:28:17 PM

Updated 6/24/2016 6:47:26 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Flagged by kiara07 [6/24/2016 1:22:56 AM], Unflagged by jeifunk [6/24/2016 6:47:21 AM], Edited by jeifunk [6/24/2016 6:47:25 AM], Confirmed by jeifunk [6/24/2016 6:47:26 AM]

s

= 8m + 6m - 4n + 3n

= 14m - n

Question

Asked 6/23/2016 11:28:17 PM

Updated 6/24/2016 6:47:26 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Flagged by kiara07 [6/24/2016 1:22:56 AM], Unflagged by jeifunk [6/24/2016 6:47:21 AM], Edited by jeifunk [6/24/2016 6:47:25 AM], Confirmed by jeifunk [6/24/2016 6:47:26 AM]

Rating

8

1/4(8m - 4n) +1/3 (6m + 3n) = 4m

2m - n + 2m + n = 2m + 2m - n + n = 4m

2m - n + 2m + n = 2m + 2m - n + n = 4m

Added 6/24/2016 1:26:05 AM

This answer has been confirmed as correct and helpful.

Find the product.
2y 2(3x + 5z) **Weegy:** 2y^2(3x + 5z) = 2y^2*3x + 2y^2*5z = 6xy^2 + 10y^2z **User:** Find the product.
x 3(x 2 + 5x + 1) **Weegy:** x^3(x^2 + 5x + 1) = x^5 + 5x^4 + x^3 (More)

Question

Updated 6/24/2016 8:35:05 AM

0 Answers/Comments

Factor p 2 + 18p + 32.

Question

Updated 6/29/2016 7:52:35 AM

1 Answer/Comment

a^2 - a - 20 = (a + 4)(a - 5)

Added 6/29/2016 7:52:35 AM

This answer has been confirmed as correct and helpful.

What is the middle term of the product of (x + 5)(x + 2)? **Weegy:** (x + 5)(x + 2)
= x^2 + 2x + 5x + 10
= x^2 + 7x + 10
The middle term is 7x. (More)

Question

Expert Answered

Updated 6/29/2016 3:01:53 PM

0 Answers/Comments

Simplify -3p3 + 5p + (-2p 2) + (-4) - 12p + 5 - (-8p3). **Weegy:** -3p^3 + 5p + (-2p^2) + (-4) - 12p + 5 - (-8p^3) = -3p^3 + 5p - 2p^2 - 4 - 12p + 5 + 8p^3; = -3p^3 + 8p^3 - 2p^2 + 5p - 12p - 4 + 5; = 5p^3 - 2p^2 - 7p + 1 (More)

Question

Updated 6/24/2016 8:14:18 AM

0 Answers/Comments

Simplify 8y(y - 4) + 3y(y + 2).
**Weegy:** 8y(y - 4) + 3y(y + 2) = 8y^2 - 32y + 3y^2 + 6y; = 11y^2 - 26y **User:** Simplify 8 + 3{x - 2[x + 5(x + 3)]}. **Weegy:** 8 + 3{x - 2[x + 5(x + 3)]} = 8 + 3{x - 2[x + 5x + 15]} = 8 + 3{x - 2x - 10x - 30} = 8 + 3x - 6x - 30x - 90 = 8 - 3x - 30x - 90 = 8 - 33x - 90 = -33x - 82 (More)

Question

Updated 6/24/2016 8:33:19 AM

0 Answers/Comments

33,070,187

questions answered

There are no comments.